Integrated optical circuits and components design and applications - Hutcheson, Lynn D. (Optical engineering (Marcel Dekker, Inc.), 1987)
This outstanding reference focuses on the practical aspects of designing, fabricating, and testing integrated optical circuits and devices -- covering everything from concepts, theory, design criteria, and materials to applications